Code-Switching in Proceedings of Civil Cases at Kuala Lumpur High Court: (Penukaran Kod dalam Prosiding Perbicaraan Kes Sivil di Mahkamah Tinggi Kuala Lumpur) (Jurnal Bahasa, 2017)
This study focuses on the phenomenon of code-switching that occurs in civil trials. For the purposes of this study, video recordings of trials at the High Court of Kuala Lumpur were used as data. Data analysis was performed based on the description and analysis of code switching by Teo Kok Seng (1996) and Wong Khek Seng (1991). The researcher focused on three kinds of code switching, that is, insertion, as well as intra- and inter-sentence code-switching. The study reveals that all three types of code-switching occur. The occurrences of code-switching are thus situational. Code-switching is due to several factors, both conscious and unconscious.Keywords: code-switching, civil suits, court, court proceedings, Malay language
Keywords: bahasa Melayu; linguistik; sosiolinguistik